Choice Decision as a Mediating Variable between Location, Price, and Tenant Satisfaction in Boarding Houses: A Perspective of Educational Service Management - Arifa Mahabbah Rosadi; Tin Agustina Karnawati; Teguh Widodo (Al-Qalam Institue, 2026)
This study aims to examine the effect of location and price on tenant satisfaction with choosing decision as a mediating variable in boarding houses located in Rungkut, Surabaya, from an educational service management perspective. Boarding houses in educational and industrial areas function as supporting services that influence students’ learning environments and overall well-being. This study adopts a quantitative approach by collecting survey data from 100 boarding house tenants, consisting of students and industrial workers. Data were gathered using a structured questionnaire measured on a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that location and price have a positive and significant effect on choosing decision. Price and choosing decision significantly influence tenant satisfaction, while location does not have a direct significant effect on tenant satisfaction. Furthermore, choosing decision is confirmed to mediate the relationship between location and tenant satisfaction as well as between price and tenant satisfaction. These findings indicate that tenant satisfaction is largely shaped by how effectively tenants evaluate and decide on boarding house options rather than by physical location alone. From an educational service management perspective, this study highlights the importance of boarding houses as part of the educational support ecosystem. The findings imply that boarding house owners and managers should emphasize transparent pricing strategies, strategic location planning, and the provision of clear and reliable decision-support information to enhance tenant satisfaction and ensure sustainable service quality in educational environments.